2010
DOI: 10.1093/mutage/geq057
|View full text |Cite
|
Sign up to set email alerts
|

Automated scoring of lymphocyte micronuclei by the MetaSystems Metafer image cytometry system and its application in studies of human mutagen sensitivity and biodosimetry of genotoxin exposure

Abstract: Automated image analysis scoring of micronuclei (MN) in cells can facilitate the objective and rapid measurement of genetic damage in mammalian and human cells. This approach was repeatedly developed and tested over the past two decades but none of the systems were sufficiently robust for routine analysis of MN until recently. New methodological, hardware and software developments have now allowed more advanced systems to become available. This mini-review presents the current stage of development and validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 23 publications
3
42
0
1
Order By: Relevance
“…Several automated systems are available on the market and have been tested by human monitoring (28,(31)(32)(33)(34). In our study the scoring system of MetaSystems (Altlussheim, Germany) was utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Several automated systems are available on the market and have been tested by human monitoring (28,(31)(32)(33)(34). In our study the scoring system of MetaSystems (Altlussheim, Germany) was utilized.…”
Section: Discussionmentioning
confidence: 99%
“…The significant achievements, current state of application, restrictions and recommendations for future research for all the above-mentioned AIC CBMN assay systems were recently addressed in a special issue of Mutagenesis (Rossnerova et al, 2011a;Decordier et al, 2011;Darzynkiewicz et al, 2011). Advances in molecular cytogenetics (e.g.…”
Section: Why Do We Need Automation In Scoring Micronuclei?mentioning
confidence: 99%
“…The first commercially available system -Metafer MNScore(MetaSystems) became a widely used platform in many laboratories during a short period of time, which is documented by various publications of users focused on the validation of technique Maes et al, 2007;Willems et al, 2010;Bolognesi et al, 2011), cancer research (Varga et al, 2005, biomonitoring studies in the field of air pollution (Rossnerova et al, 2009(Rossnerova et al, , 2011a, radiation biodosimetry (Thierens and Vral, 2009;Willems et al, 2010) and in cell lines in in vitro studies (Cariou et al, 2010;Doherty et al, 2011). This system, first introduced in 2004 ( Schunck et al, 2004), allows the automatic detection of mononucleated and binucleated (BN) cells based on proximity of nuclei and morphology, and the consequent automated detection of MN, identified by their morphology, in a defined area of interest around the nuclei of the selected BN cells.…”
Section: Current Developments In Automation Of Micronucleus Assays Bymentioning
confidence: 99%
“…A recent study involving 22 patients with rectal cancer showed no significant difference between the dicentric assay and the micronucleus assay after radiochemotherapy [11]. In terms of a diagnostic technique, scoring for the CBMN technique is quick, simple and can be automated for use in a mass casualty situation [12,13]: a distinct advantage over the dicentric assay, which is a timeconsuming process requiring expert personnel. Automation, however, does not include centromere-negative micronuclei or NPB in its scoring: features that increased its sensitivity in biodosimetry [14].…”
Section: The Micronucleus Assaymentioning
confidence: 99%